Leptospira sp. vertical transmission in ewes maintained in semiarid conditions - Nogueira, Denise Batista; da Costa, Flávia Teresa Ribeiro; de Sousa Bezerra, Camila; Soares, Rafael Rodrigues; da Costa Barnabé, Nathanael Natércio; Falcão, Brunna Muniz Rodrigues; Silva, Maria Luana Cristiny Rodrigues; da Costa, Diego Figueiredo; Araújo, João Pessoa [UNESP]; Malossi, Camila Dantas [UNESP]; Ullmann, Leila Sabrina [UNESP]; Alves, Clebert José; et al. (Elsevier, 2020)
Leptospirosis is a globally distributed disease associated with reproductive failures in livestock; however, its pathogenesis has not been fully elucidated. Results from the present study indicate there is a presence of Leptospira sp. in organs and fluids of fetuses from ewes slaughtered in the semiarid region of Brazil. Twenty-nine fetuses from 23 ewes determined to be Leptospira sp.-positive using PCR were sampled (14 and 15 in dry and rainy seasons, respectively). Fetal samples of blood, central nervous system (CNS), lung, liver, spleen, stomach contents, peritoneal fluid, kidney, bladder, urine and reproductive system were collected. Diagnostic methods included the microscopic agglutination test (MAT), polymerase chain reaction (PCR) and bacterial isolation. Of the 29 fetuses, 24 (82.8 %) had at least one Leptospira sp.-positive organ or fluid, as determined using PCR, and of a total of 209 samples, 62 (29.7 %) contained leptospiral DNA. Of the 99 samples collected during the dry season, 42 (42.4 %) were positive, and of 110 samples collected during the rainy season, 20 (18.2 %) were positive (P = 0.0001). There was deoxyribonucleic acid (DNA) sequencing of three samples of kidney, CNS and liver, and in all of these, there was 99.3 % similarity with Leptospira interrogans. Leptospires were present in cultures of pooled samples from fetuses with deformities. Results indicate there is vertical (maternal-to-fetus) transmission which would represent an alternative transmission route for the spread of Leptospira sp. in ewes, suggesting molecular detection is essential in the investigation of leptospirosis in fetuses to identify animals that have been infected with this bacterium.
Keywords: Direct transmission; Extrarenal leptospirosis; Fetuses; PCR; Placenta